The responsibility of the state for the violation of the constitutional and human rights of persons deprived of Liberty without a sentence in Ecuador - Guevara León , Diego Eduardo (2023)
Ecuador is characterized by being a Constitutional State of Rights and Justice, it has signed and ratified several intentional human rights agreements, which oblige the Government to adopt measures to avoid the violation of fundamental and human rights. The inadequate social rehabilitation system, the lack of application of the law and constitutional guarantees, prison overcrowding, the insufficient budget, the lack of old infrastructure, the lack of specialized human talent, the insecurity and violence that prevails within the country of rehabilitation centers, among other facts, are the fundamental causes for there to be a repeated violation of rights. The purpose of the manuscript is to analyze the responsibility of the State for the violation of the constitutional and human rights of people deprived of liberty without sentence, for this purpose a critical study of the doctrine, the norm and the jurisprudence was carried out. The research is located in the social rehabilitation centers of Ecuador; For its study, the mixed approach is assumed; The inductive, historical-logical, dogmatic and descriptive legal method is used; Due to the objectives they achieve, it is a pure, analytical legal and descriptive legal investigation; non-experimental design; The population involved is made up of authorities and directors of the Social Rehabilitation Centers of Ecuador, of the National Service of Comprehensive Care for Adults Deprived of Liberty and Adolescents SNAI and Judges of Constitutional and Penitentiary Guarantees, to whom a questionnaire was applied. closed questions; The results indicate that in the prison centers of Ecuador, there is no humane treatment without discrimination, it does not respect and guarantee personal integrity and there is no effective protection of the rights of people deprived of liberty without a sentence, which is why He concludes by pointing out that the Ecuadorian State is primarily responsible for the aforementioned, because there is no adequate control of the prisons, nor is there efficient management of the Social Rehabilitation Centers.